The path that Allah made - Jafri, Adeeba (Goodword Books New Delhi, 2003)
"The Path that Allah Made is a beautiful illustrated poem that extolls the beauty of Allah's Creation. Allah has made this vast earth with plentiful provisions. We must explore the path that Allah has made, and be thankful to Him for providing sustenance for us"--Publisher's website, viewed July 19, 2012